Mapping monoclonal anti-SARS-CoV-2 antibody repertoires against diverse coronavirus antigens - de Souza, Matheus Oliveira; Madan, Bharat; Teng, I-Ting; Huang, Aric; Liu, Lihong; Fahad, Ahmed S.; Lopez Acevedo, Sheila N.; Pan, Xiaoli; Sastry, Mallika; Gutierrez-Gonzalez, Matias; Yin, Michael T.; Zhou, Tongqing; et al. (Frontiers in Immunology, 2022)
Variants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have emerged continuously, challenging the effectiveness of vaccines, diagnostics, and treatments. Moreover, the possibility of the appearance of a new betacoronavirus with high transmissibility and high fatality is reason for concern. In this study, we used a natively paired yeast display technology, combined with next-generation sequencing (NGS) and massive bioinformatic analysis to perform a comprehensive study of subdomain specificity of natural human antibodies from two convalescent donors. Using this screening technology, we mapped the cross-reactive responses of antibodies generated by the two donors against SARS-CoV-2 variants and other betacoronaviruses. We tested the neutralization potency of a set of the cross-reactive antibodies generated in this study and observed that most of the antibodies produced by these patients were non-neutralizing. We performed a comparison of the specific and non-specific antibodies by somatic hypermutation in a repertoire-scale for the two individuals and observed that the degree of somatic hypermutation was unique for each patient. The data from this study provide functional insights into cross-reactive antibodies that can assist in the development of strategies against emerging SARS-CoV-2 variants and divergent betacoronaviruses.